Language semantics in Azerbaijan’s Folklore Examples of the dramatic art of well-known Azerbaijani writer Ilyas Efendiyev - Namazova, Flora Kamran (International Journal of Psychosocial Rehabilitation, 2020)
The need for a more detailed study of Ilyas Efendiyev’s creativity is also associated with the richness of the language and style of this author. In general, the problems of the language and style of the literary process should be studied in a comprehensive manner, and only in this case can we solve a number of important and new problems associated with linguistic creativity. This may contribute to the emergence of new language features, in the content and richness of form. It should be noted that the linguistic and stylistic features of Ilyas Efendiyev’s dramatic art have not been studied enough in Azerbaijani linguistics Type of Paper— Review